Methylation-associated partial down-regulation of mesothelin causes resistance to anti-mesothelin immunotoxins in a pancreatic cancer cell line - Hollevoet, Kevin; Mason-Osann, Emily; Müller, Fabian; Pastan, Ira (PLoS ONE, 2015)
Anti-mesothelin Pseudomonas exotoxin A-based recombinant immunotoxins (RITs) present a potential treatment modality for pancreatic ductal adenocarcinoma (PDAC). To study mechanisms of resistance, the sensitive PDAC cell line KLM-1 was intermittently exposed to the anti-mesothelin SS1-LR-GGS RIT. Surviving cells were resistant to various antimesothelin RITs (IC50s >1 μg/ml), including the novel de-immunized RG7787. These resistant KLM-1-R cells were equally sensitive to the anti-CD71 HB21(Fv)-PE40 RIT as KLM-1, indicating resistance was specific to anti-mesothelin RITs. Mesothelin gene expression was partially down-regulated in KLM-1-R, resulting in 5-fold lower surface protein levels and decreased cellular uptake of RG7787 compared to KLM-1. Bisulfite sequencing analysis found that the mesothelin promoter region was significantly more methylated in KLM-1-R (59 ± 3.6%) compared to KLM-1 (41 ± 4.8%), indicating hypermethylation as a mechanism of mesothelin downregulation. The DNA methyltransferase inhibitor 5-azacytidine restored original mesothelin surface expression to more than half in KLM-1-R and increased sensitivity to RG7787 (IC50 = 722.4 ± 232.6 ng/ml), although cells remained significantly less sensitive compared to parental KLM-1 cells (IC50 = 4.41 ± 0.38 ng/ml). Mesothelin cDNA introduction in KLM-1-R led to 5-fold higher surface protein levels and significantly higher RG7887 uptake compared to KLM-1. As a result, the original sensitivity to RG7787 was fully restored (IC50 = 4.49 ± 1.11 ng/ml). A significantly higher RG7787 uptake was thus required to reach the original cytotoxicity in resistant cells, hinting that intracellular RIT trafficking is also a limiting factor. RNA deep sequencing analysis of KLM-1 and KLM-1-R cells supported our experimental findings; compared to KLM-1, resistant cells displayed differential expression of genes linked to intracellular transport and an expression pattern that matched a more general hypermethylation status. In conclusion, resistance to anti-mesothelin RITs in KLM-1 is linked to a methylation-associated down-regulation of mesothelin, while aberrations in RIT trafficking could also play a role.
CRIS-Team Scopus Importer:2024-12-02